2011
DOI: 10.1111/j.1365-3113.2011.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions of the cytochrome c oxidase DNA barcoding region

Abstract: Enzymatic amplification of homologous regions of DNA using ‘universal’ polymerase chain reaction primers has provided insight into insect systematics, phylogeography, molecular evolution and species identification. One of the more commonly amplified and sequenced regions is a short region of the cytochrome c oxidase subunit I gene (COI), commonly called the barcoding region. COI is one of three mitochondrial‐encoded subunits of complex IV (Cox) of the electron transport chain. In addition to the mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…; Puslednik et al. ; Zhang and Broughton ; Parmakelis et al. ), although this is likely to become an area of interest as more nuclear sequence becomes available.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…; Puslednik et al. ; Zhang and Broughton ; Parmakelis et al. ), although this is likely to become an area of interest as more nuclear sequence becomes available.…”
Section: Reviewmentioning
confidence: 99%
“…However, interested readers are directed to general introductions to the field of protein co-evolution (Lovell and Robertson 2010;Fares et al 2011). To date, only a handful of co-evolutionary analyses have been applied to mitochondrial complexes (Goldberg et al 2003;Gershoni et al 2010;Garvin et al 2011;Puslednik et al 2012;Zhang and Broughton 2013;Parmakelis et al 2014), although this is likely to become an area of interest as more nuclear sequence becomes available. We performed a statistical coupling analysis (SCA) that identified several sites within the ND5 protein that appeared to strongly co-evolve with other sites that showed a signal for positive selection (Garvin et al 2011).…”
Section: Reviewmentioning
confidence: 99%
“…Amino acid substitution tables can be built from different structural environments, for example, solvent accessible and inaccessible regions within proteins of known tertiary structure, and be used for constructing refined and better supported evolutionary trees ( Overington et al 1990 ; Thorne et al 1996 ; Gong and Blundell 2008 ). In addition, if the tertiary structure is known for one of the sequences in an amino acid alignment it can be used to infer the structural environments for the other sequences (e.g., Mizuguchi et al 1998 ; Melvin et al 2008 ; Puslednik et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…2015 ). More than 70 nuclear-encoded subunits of these complexes appear to coevolve with the mitochondrial-encoded subunits ( Gershoni et al 2010 ; Garvin et al 2011 , 2015 ; Puslednik et al 2012 ; Parmakelis et al 2013 ; Zhang and Broughton 2013 ) and it has also been recently shown that complexes I, III, and IV form higher order structures called “supercomplexes” ( Dudkina et al 2011 ; Lapuente-Brun et al 2013 ) that enhance respiration, possibly by decreasing the distances among active sites ( Kadenbach 2012 ) or improving the stability of complexes ( Blaza et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%